Disentangling the role of social cognition processes at early steps of alcohol abuse: The influence of affective theory of mind. (March 2020) - Lannoy, Séverine; Gilles, Fanny; Benzerouk, Farid; Henry, Audrey; Oker, Ali; Raucher-Chéné, Delphine; Besche-Richard, Chrystel; Gierski, Fabien
Highlights: Alcohol use and binge drinking in adolescence are important public health concerns. Research has explored the psychological factors related to early alcohol abuse. Few studies have investigated the role of social cognition. We evaluated empathy and theory of mind to predict early alcohol abuse. Affective theory of mind predicted specific binge drinking in adolescents. Abstract: Excessive alcohol use among adolescents has become a pressing challenge among Western societies. Accordingly, one of the current research objectives is to identify the processes associated with this harmful habit. Although numerous studies have underlined the role of executive and motivational processes, few have explored emotional and interpersonal abilities at early steps of alcohol abuse. The present study evaluated the role of two social cognition processes, namely theory of mind (ability to infer others' mental states at cognitive and affective levels) and empathy (ability to understand others' feelings at cognitive and affective levels) in adolescents' alcohol consumption. Two hundred and two adolescents (13–20 years old) performed a behavioral task evaluating theory of mind and filled in questionnaires measuring personal data, empathy, alcohol consumption (alcohol abuse and specific binge drinking), as well as depressive and anxiety symptoms. Findings showed that cognitive and affective empathy were negatively associated with alcohol consumption in youth whereas affective theory of mind was related to specific binge drinking. Importantly, affective theory of mind predicted binge drinking in adolescents, even after controlling for age, gender, and education level. These results emphasized the role of social cognition in early alcohol abuse and showed that, beyond inhibition, interpersonal abilities might precipitate excessive drinking in youth.